The manifestation of the history of the kurdish princes in the poetry of haji qadir al-koyi - Pashbadi, Yadullah (Humanities Journal of University of Zakho, 2023)
Haji Kadir al-Koyi (1817-1897), as a popular poet who was educated in Kurdish literature, was interested in history, culture and technology. In the second period of his poetic life, he was concerned with the Kurdish scholars, princes, and associates, and identified their most important features and services. This research seeks, in the light of the descriptive-analytical approach, to pay attention to the historical dimensions of Haji’s poetry related to the family of princes and rulers, and to examine their governmental and social features and characteristics within his poems, and tries to delve into the sources of Haji Qadir and the springs of his ideas. Haji was closely related to newspapers and technology news arriving from Europe, and in the meantime he referred to the achievements of the Kurdish princes and their role in different eras, and their interests in poetry and literature.